Integration of explicit vocabulary instruction in teaching Science - Venida, Ariel (Journal of research, policy & practice of teachers & teacher education, 2021)
Reading comprehension is an essential interdisciplinary skill that serves as a foundation of all other subject areas. In science, as a subject rich in vocabulary words, the learner's ability to read and comprehend to generate a conceptual understanding cannot be set aside. Thus, integrating literacy strategies such as vocabulary instruction strategies in teaching the subject is of great help to the learners. This quasi-experimental research determined the effect of integrating explicit vocabulary instruction strategy in the conceptual understanding of students in science. Forty-four students served as participants in this research. Inquiry-based approach, particularly the Engage, Explore, Explain, Elaborate, and Evaluate Learning Cycle (5 E’s) was utilized in teaching the control group. While in the experimental group, the same strategy was employed, but with the integration of vocabulary instruction strategies. T-test was used in determining the significant difference in the performances of the two groups. The findings reveal that the students who were taught with the integration of explicit vocabulary instruction strategy performed better than the students who did not undergo vocabulary instruction. This suggests that the integration of the explicit vocabulary instruction strategy in teaching science enhances the conceptual understanding of the students in the subject. Thus, it is recommended that science teachers who are trained as content specialists should consider integrating explicit vocabulary instruction strategies in teaching to address the literacy needs of the students.